Sustainability of Local Government Laws and Sports Services in Turkey - Bingolbali, Abdullah (Lahore Medical Research Center Llp, 2021)
Background: Sustainability is a concept that has been frequently heard and therefore given importance recently. Ecological changes occurring today, ever-increasing excessive consumption habits, unstoppable population growth rate and economic developments have caused this concept to become widespread. Therefore, states have had to act by considering their continuity and future in the planning of all kinds of services to be offered to the public. Aim: The aim of this study is to determine the dimensions of sustainability in local government laws in the field of sports and its effect on sports services. Methods: The case studies design was used in the study, which was designed according to the qualitative research model. Herein, in accordance with the purpose of the research document review and scanning method, which are the data collection methods, were used. It is aimed to reach more sources by analyzing the written materials containing information about the targeted phenomenon or cases. Results: When local government laws are examined in terms of economic and environmental sustainability, there are no explanatory and satisfactory explanations regarding these issues. Conclusion: It cannot be said that local government laws on sports and sports services are satisfactory in terms of social, and economic sustainability
Keywords: Sustainability; Local Governments; Sports Services; Rural Areas; Turkey